Early Language Education in Instructed Contexts: Current issues and empirical insights into teaching and learning languages in primary school (Language Learning & Language Teaching, 2025)
This volume presents state-of-the-art research in early foreign language (L2) education in instructed contexts with a special focus on primary school (ages 5-12). Over the past two decades, early language teaching has become an important factor in both academic inquiry and education policy. Studies have attested to the value of early L2 learning but also revealed specific features and challenges, which highlights the need for more high-quality empirical research. This book addresses this need by presenting current international research on early L2 teaching and learning in regular and CLIL contexts in the primary school setting. Uniting insights from 12 countries, the studies shed light on current issues such as teaching and assessment practice, emerging L2 literacy instruction, teaching materials, and teachers’, parents’ and learners’ perspectives. The volume thus contributes significantly to the advancement of early language education and is an essential resource for researchers and educators in the field.